Shift in the submucosal microbiome of diseased peri-implant sites after non-surgical mechanical debridement treatment - Sun, Fei; Wei, Yiping; Li, Siqi; Nie, Yong; Wang, Cui; Hu, Wenjie (Frontiers in Cellular and Infection Microbiology, 2023)
Objectives The object of this prospective study was to assess the submucosal microbiome shifts in diseased peri-implant sites after non-surgical mechanical debridement therapy. Materials and methods Submucosal plaques were collected from 14 healthy implants and 42 diseased implants before and eight weeks after treatment in this prospective study. Mechanical debridement was performed using titanium curettes, followed by irrigation with 0.2% (w/v) chlorhexidine. Subsequently, 16S rRNA gene sequencing was used to analyze the changes in the submucosal microbiome before and after the non-surgical treatment. Results Clinical parameters and the submucosal microbiome were statistically comparable before and after mechanical debridement. The Alpha diversity decreased significantly after mechanical debridement. However, the microbial richness varied between the post-treatment and healthy groups. In network analysis, the post-treatment increased the complexity of the network compared to pre-treatment. The relative abundances of some pathogenic species, such as Porphyromonas gingivalis, Tannerella forsythia, Peptostreptococcaceae XIG-6 nodatum, Filifactor alocis, Porphyromonas endodontalis, TM7 sp., and Desulfobulbus sp. HMT 041, decreased significantly following the non-surgical treatment. Conclusions Non-surgical treatment for peri-implant diseases using mechanical debridement could provide clinical and microbiological benefits. The microbial community profile tended to shift towards a healthy profile, and submucosal dysbiosis was relieved following mechanical debridement.